2022
DOI: 10.1097/iae.0000000000003352
|View full text |Cite
|
Sign up to set email alerts
|

Chorioretinal Atrophy in Vitreoretinal Lymphoma

Abstract: This study revealed the frequency, risk factors, and functional prognosis of chorioretinal atrophy associated with vitreoretinal lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In our case, the postoperative IOP was 16 mm Hg lower than the preoperative IOP. Unlike other surgeries or procedures commonly associated with ODR, such as trabeculectomy, glaucoma drainage implantation, and iridotomy, phacoemulsification, which was performed in this case, is rarely associated with ODR [1] . In this patient, the hemorrhage occurred in the intraretinal and preretinal areas.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our case, the postoperative IOP was 16 mm Hg lower than the preoperative IOP. Unlike other surgeries or procedures commonly associated with ODR, such as trabeculectomy, glaucoma drainage implantation, and iridotomy, phacoemulsification, which was performed in this case, is rarely associated with ODR [1] . In this patient, the hemorrhage occurred in the intraretinal and preretinal areas.…”
Section: Discussionmentioning
confidence: 80%
“…However, the chemotherapeutic drugs might also have played a role via a toxic effect on the retinal vessels. ODR manifests as diffuse retinal hemorrhages following an acute lowering of the IOP [1] . Studies have revealed that the mean IOP decrease in ODR is 33.2±15.8 mm Hg (range, 4-57 mm Hg), with 82% of ODR events occurring on the first postoperative day [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A worse visual outcome after treatment for VRL with subretinal infiltration and exudative retinal detachment is considered to result in RPE atrophy with secondary photoreceptor dysfunction 18 . Alessandro et al 19 reported that 52% (41 eyes of 79 eyes) of their VRL cohort showed chorioretinal atrophy (CRA) and the eyes with CRA had a significantly worse vision. Major risk factors of developing CRA were retinal infiltrates, vertical hyperreflective lesions, and macular involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, VRL can affect retinal periphery without macular involvement, and OCT scans can eventually report no signs of retinal involvement. 32 , 37 40 …”
Section: Multimodal Imagingmentioning
confidence: 99%